FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN ULANG PASIEN HIPERTENSI DI PUSKESMAS SUKAMULYA KABUPATEN KUNINGAN - Denny Mustafa; Rossi Suparman; Lely Wahyuniar; Mamlukah (Journal of Midwifery and Health Administration Research, 2023)
Background: According to WHO, an estimated 9.4 million people in the world who suffer from hypertension with various complications and comorbidities die consistently. Information obtained in 2018 more than 427,218 people in Indonesia died due to hypertension. This study aimed to find out what factors influenced the repeat visits of hypertensive patients at the Sukamulya Health Center, Kuningan Regency. Methods: The research used is analytic with a cross sectional design. The subjects in this study were hypertensive patients at the Sukamulya Health Center in January-August 2022 with a total of 3,830 patients, using the Random Smpling sampling technique and a sample of 362 samples were obtained based on inclusion and exclusion criteria. The research data were processed and analyzed using the Chi Square test for bivariate analysis and logistic regression for multivariate analysis. Result: The distribution of hypertension patients at the Sukamulya Health Center who made repeat visits was 263 patients and 99 patients did not make repeat visits. Based on the Chi Square test, it was found that there was a relationship between the provision of education, pharmacological therapy and the referral system with repeat visits of hypertensive patients at the Sukamulya Health Center (p value <0.05). The most dominant factor influencing the return visit of hypertensive patients was pharmacological therapy with OR = 39,682. Conclusion: Factors providing education, pharmacological therapy and the referral system have an influence on the repeat visits of hypertensive patients at the Sukamulya Health Center in 2022. Therefore it is important for patients to make repeat visits to hypertension as well as for the puskesmas to be able to provide standardized hypertension services for patients.